Designing bryophyte surveys for an optimal coverage of diversity gradients - Medina, Nagore G; Lara, Francisco; Mazimpaka, Vicente; Hortal, Joaquin (BIODIVERSITY AND CONSERVATION, 2013)
Knowledge on the distribution and abundance of species is plagued by significant taxonomic and geographic biases that influence the analyses on biodiversity patterns. Due to this, standard, easy-to-use methods are needed to design efficient field campaigns that minimize data deficiencies. We evaluate the applicability, usefulness and effectiveness of a survey design protocol based on the Environmental Diversity (ED) criterion under different scenarios, with examples of varying extent of environmental niche, range of spatial distribution and level of previous knowledge. We planned surveys for epiphytic bryophytes growing in three types of forests at NW Iberian Peninsula (dominated by Quercus ilex, Q. faginea and Q. pyrenaica). Knowledge on the distribution and abundance of epiphytic bryophytes in this region presents large gaps and strong geographic biases. Besides, the three forest types differ in their environmental requirements, spatial distribution and level of previous knowledge, providing three working scenarios to test the response of the protocol under different situations. The protocol was implemented as a set of sequential selection rules, starting by an ED-based criterion aiming at maximizing the coverage of climatic and geographic variability; further criteria include an iterative set of qualitative properties: maximizing forest area, conservation status and accessibility. The protocol performed efficiently at different ranges of spatial distribution levels of environmental variability, and degree of previous knowledge and generated an even distribution of sampling points that efficiently covered the diversity of epiphytic bryophytes. The results show that ED protocols are a proficient and time-saving approach to select sampling sites by objective criteria also for groups with high dispersal ability and fragmented landscapes.
Keywords: diversity; ED protocol; epiphytic bryophytes; Mediterranean; method; p-Median; Quercus forests; Sampling design

A new species of Metabelbella (Acari: Oribatida: Damaeidae) from Quercus forests of southern Portugal - Ermilov, Sergey G.; Shtanchaeva, Umukusum Y.; Subías, Luis S. (International Journal of Acarology, 2012)
In the course of studies of the oribatid fauna of oak forests from southern Portugal, we found representatives of 60 species (51 genera and 38 families) of which 39 species are registered for the first time for Portugal. One new species, Metabelbella epidamaeiformis sp. nov., is described. It is clearly distinguishable from all other species of the genus by the presence of spinae adnatae. An identification key to known Iberian species of Metabelbella is presented. A checklist, the locality and the distribution of all oribatid taxa recorded by us are presented.
doi: 10.1080/01647954.2011.645284doi: 10.1080/01647954.2011.645284The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: checklist; fauna; key; Metabelbella; new species; Oribatida; Portugal; Quercus forests

Quercus and Pinus cover are determined by landscape structure and dynamics in peri-urban Mediterranean forest patches - Guirado, Maria; Pino, Joan; Rodà, Ferran; Basnou, Corina (Plant Ecology, 2007)
Successional dynamics in Mediterranean forests have been modulated by anthropogenic disturbances during thousands of years, especially in areas densely populated since ancient times. Our objective is to determine whether pine tree cover (early-successional species) and oak tree cover (late-successional species), used as a surrogate of successional stage of peri-urban fragmented forests in the Valle`s lowlands (Catalonia, NE, Spain), are primarily determined by (1) climate and topography; (2) anthropogenic disturbances; (3) patch structure; or (4) patch dynamics from 1956 to 1993. Quercus spp. and Pinus spp. tree cover were separately recorded on 252 randomly selected plots of 100 m 2 , within forest patches ranging in size from 0.25 to 218 ha. Multiple linear regressions indicated that forest patch history is the most important variable determining oak and pine tree cover: new forest patches showed higher pine and lower oak tree cover than recently split patches (i.e. those that became fragmented from large forest areas after 1956). Patches already existing as such in 1956 (pre-existent patches) showed higher pine cover than recently split patches. Oak cover increased and pine cover decreased with increasing forest connectivity of the patch. Finally, highly frequented forests were related to high cover of pines. Climatic and topographic variables were not signiﬁcant. We conclude that pine and oak cover in these peri-urban forests are mainly determined by recent patch dynamics, but also by the spatial pattern of patches. However, humaninduced disturbance can modulate this as there is some evidence for pine being associated with a high human frequentation.
Keywords: á pinus; á quercus forests; anthropogenic disturbances; anthropogenic disturbances á forest; Forest fragmentation; forests á patch structure; fragmentation á historical dynamics; historical dynamics; patch structure; pinus forests; Quercus forests